Desenvolvimento de método para determinação de anfetaminas e benzoilecgonina em amostras de cabelo por LC-MS/MS - Breno Frederico Pereira Paulo (2017)
In recent years, hair drug testing has gained importance in determination of substances of abuse. This type of analysis stands out because has a wider detection window than urine and, therefore, is a valuable appliance in the evaluation of the recent history of drugs of abuse in post-mortem analysis, workplace drug test, renewal of license to drive in case of professional drivers and for monitoring patients in phase of social reinsertion. Therefore, it is necessary to develop analytical methods able to detect these substances in hair to meet the current demand for this type of analysis. In this work a simple and fast method was developed to detect benzoylecgonine, amphetamine, methamphetamine, MDA, MDMA and MDEA by liquid chromatography tandem mass spectrometry in hair samples. The method was optimized and used the micropulverization of the hair samples, followed by extraction with acidified methanol, to favor the extraction of the drugs more quickly. Then the method was validated for: linearity from 0.020 ng mL-1 to 4,000.0 ng mL-1; and obtained intra and inter-assay accuracy lower than 8.1% and 11.4%, respectively. The limits of detection and quantification obtained were 0.012 ng mg-1 and 0.020 ng mg-1, respectively, for all analytes. After validation, the methods was applied to 14 real samples from rehabilitation center, volunteers and the Legal Medical Institute of Belo Horizonte / MG.